Cobalt‐containing bioactive glass mimics vascular endothelial growth factor A and hypoxia inducible factor 1 function. Issue 7 (11th September 2020) - de Laia, Andréia Grossi Santos; Valverde, Thalita Marcolan; Barrioni, Breno Rocha; Cunha, Pricila da Silva; de Goes, Alfredo Miranda; de Miranda, Marcelo Coutinho; Gomes, Dawidson Assis; Queiroz‐Junior, Celso Martins; de Sá, Marcos Augusto; de Magalhães Pereira, Marivalda
Abstract: Bioactive glasses (BGs) have shown great potential for tissue regeneration and their composition flexibility allows the incorporation of different ions with physiological activities and therapeutic properties in the glass network. Among the many ions that could be incorporated, cobalt (Co) is a significant one, as it mimics hypoxia, triggering the formation of new blood vessels by the vascular endothelial growth factor A ( VEGFA ), due to the stabilizing effect on the hypoxia inducible factor 1 subunit alpha ( HIF1A ), an activator of angiogenesis‐related genes, and is therefore of great interest for tissue engineering applications. However, despite its promising properties, the effects of glasses incorporated with Co on angiogenesis, through human umbilical cord vein endothelial cells (HUVECs) studies, need to be further investigated. Therefore, this work aimed to evaluate the biocompatibility and angiogenic potential of a new sol–gel BG, derived from the SiO2 –CaO–P2 O5 –CoO system. The structural evaluation showed the predominance of an amorphous glass structure, and the homogeneous presence of cobalt in the samples was confirmed. in vitro experiments showed that Co‐containing glasses did not affect the viability of HUVECs, stimulated the formation of tubes and the gene expression of HIF1A and VEGFA . in vivo experiments showed that Co‐containing glasses stimulated VEGFA and HIF1A expression in blood vessels and cell nuclei, respectively, in the deep dermis layer of the dorsal region of rats, featuring considerable local stimulation of the angiogenesis process due to Co‐release. Co‐containing glasses showed therapeutic effect, and Co incorporation is a promising strategy for obtaining materials with superior angiogenesis properties for tissue engineering applications. Abstract :